Onion Essential Oil-in-Water Emulsion as a Food Flavoring Agent : Effect of Environmental Stress on Physical Properties and Antibacterial Activity - Elham, Taghavi; Afifah Syazwani, Abdul Salam; Navideh, Anarjan; Elexson, Nillian; Mohd Nizam, Lani (Hindawi Publishing, 2022)
Plant essential oils (EOs), which are acknowledged as generally recognized as safe (GRAS) by the Food and Drug Administration (FDA), have the potential to be used as a flavoring agent. However, there are limitations to some EOs, such as low water solubility and high volatility, which limit their application in food technology. This study was conducted to develop onion (Allium cepa) EO as a flavoring agent and determine its stability against environmental stress via an emulsification technique, with different concentrations of sodium caseinate, as a delivery system. Emulsions containing onion EO were prepared using different concentrations of sodium caseinate (3, 5, and 7% w/w) via the solvent-displacement technique. The physical properties (average droplet size, color, turbidity, and stability measurement) and antibacterial activity (agar disk diffusion method) of emulsions were then determined. Results show that emulsion with 7% (w/w) sodium caseinate was the most desirable sample in terms of physical properties and antibacterial activity. Hence, it was selected for environmental stress studies (i.e., thermal processing, freeze-thaw cycles, and ultraviolet (UV) exposure). Results revealed that all types of environmental stresses had significant (p < 0:05) effects on droplet size, color, turbidity, and stability. Generally, the environmental stresses increased the droplet size except in the freeze-thaw cycle case, while all stresses decreased the stability and lightness. All types of environmental stress treatment did not show a significant (p < 0:05) effect on antibacterial activity enhancement against Salmonella Typhimurium and Listeria monocytogenes except in the case of UV treatment against L. monocytogenes. Therefore, the present work has demonstrated the potential use of emulsion as an encapsulation and delivery system of EO flavors for food applications.